Gene expression of psychiatric disorder-related kinesin superfamily proteins (Kifs) is potentiated in alternatively activated primary cultured microglia - Suguru Iwata; Mitsuhiro Hyugaji; Yohei Soga; Momo Morikawa; Tetsuya Sasaki; Yosuke Takei (BMC Research Notes)
Abstract Objective Reactivity of microglia, the resident cells of the brain, underlies innate immune mechanisms (e.g., injury repair), and disruption of microglial reactivity has been shown to facilitate psychiatric disorder dysfunctions. Although cellular analyses based on cultured microglia have been conducted, the molecular mechanism regulating microglial polarization remains elusive. We established a primary microglia culture that enabled manipulation of the substate of cells. This allowed us to investigate the expression levels of psychiatric disorder-related Kifs messenger RNA (mRNA) in each condition. Kifs encode molecular motor proteins that transport cargo along microtubules, which are thought to dynamically reorganize during a substate change. Results As a candidate for a crucial Kifs gene that is associated with microglia polarization, we selected psychiatric disorder-related Kifs including Kif17. We found that the relative amounts of Kif3a, Kif17, and Kif13a mRNA were potentiated in alternatively activated microglia, whereas there were no significant changes in activated microglia. Furthermore, the microglia derived from a mouse line which possesses a mutation inducing truncated KIF17 indicated disrupted morphological phenotype of alternatively activated microglia. These results suggest that the potentiation of specific molecular motor expression is required to maintain the function of alternatively activated microglia.